2021
DOI: 10.1519/ssc.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Ketogenic Diet on Anthropometric Parameters, Metabolic Adaptation, and Physical Fitness Performance in Amateur Endurance Athletes: A Systematic Review

Abstract: Implementing ketogenic diets (KDs) in endurance athletes is currently an interesting topic. This article aimed to systematically review the effects of KDs on anthropometric, metabolic, and performance parameters in endurance sport athletes, highlighting the recommendations about how they should be used. This systematic review was performed under Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and it was performed using 2 databases (i.e., PubMed and Web of Sciences). From the 1,48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Regarding exercise performance, the most recent systematic reviews, including or not meta-analysis, showed that the ketogenic diet does not produce better effects compared with carbohydrate-based diets in both aerobic (e.g. cycling and running) and strength performances [7 ▪ ,9] and seems to have no effect in improving endurance performance even when combined with concurrent training [8].…”
Section: Exercise Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding exercise performance, the most recent systematic reviews, including or not meta-analysis, showed that the ketogenic diet does not produce better effects compared with carbohydrate-based diets in both aerobic (e.g. cycling and running) and strength performances [7 ▪ ,9] and seems to have no effect in improving endurance performance even when combined with concurrent training [8].…”
Section: Exercise Performancementioning
confidence: 99%
“…Over the decades, several studies have been conducted about the effects of the ketogenic diet on exercise performance in different modalities and exercise modes, and on the body composition in diverse populations. Concerning this issue, there were several studies with meta-analyses published recently [7 ▪ ,8–10]. They all showed no advantage of the ketogenic diet over normal/high carbohydrate-based diets on physical performance.…”
Section: Introductionmentioning
confidence: 99%